A riqueza do império: Francisco Arango y Parreño, economia política e a segunda escravidão em Cuba - Tomich, Dale (Revista de História, 2003)
This article examines the use of Enlightenment political economy by Francisco Arango y Parreño's - planter, statesman, and spokesman for the Havana elite - to reconceptualize national wealth, slavery, and free trade in order to establish the theoretical ground for Cuba's domination of the world sugar market. It demonstrates that Arango's pro-slavery position and Adam Smith's critique of slavery constitute contradictory aspects of liberal political economy in the conjuncture of nineteenth century world market.